樂齡學習者課程參與情形與幸福感、寂寞感及自尊間的關聯 Well-being, Loneliness and Self-esteem in Lifelong Learning: The Role of Engagement - 郭郡羽 Chun-Yu Kuo; 王美文 Mei-Wen Wang; 張德永 Te-Yung Chang (National Taiwan Normal University, 2021)
在高齡社會的趨勢下，高齡者的心理健康相關議題日益重要。透過終身學習能使高齡者不斷參與活動、活化大腦、增加人際連結，對高齡者的心理健康有相當大的助益。在這當中，什麼樣的高齡學習者最快樂呢？本研究目的即以初探性的方式勾勒出高齡學習者的樣貌，藉由發放837份問卷評估樂齡學習中心高齡者的幸福感、寂寞感及自尊，並針對高齡者參與課程的時間、課程的多元性及在學習中擔任身分的多元性將高齡者進行分類，觀察上述參與型態對高齡學習者的影響。結果發現，參與課程時間愈長者，幸福感及自尊都愈高；參與課程愈多元者，寂寞感較低；而身分愈多元者除幸福感、自尊較高外，寂寞感亦較低。本研究試著描繪出高齡學習者的學習特徵與各項重要心理適應變項間的關聯，發現能夠持續參與課程、多元學習及在學習過程中同時擔任多元角色的高齡者心理健康較佳。根據此研究結論，建議樂齡學習中心為高齡長輩開設課程時能關注高齡者持續參與的情形，並鼓勵參與多樣化的課 程，並由學員回流成為課程助教或擔任中心志工以增加多元的角色，期使高齡者能更樂在學習中。 The present and the future of our society are shaped by an increasing proportion of the elderly population. In the context of the global population aging, mental health concerns are more critical than ever. Lifelong learning provides opportunities for maintaining the mental health of older people. older people can continue to participate in courses to maintain their cognitive functions and increase interpersonal connections. The present study developed a profile of the characteristics of older learners at a older people learning center. We examined the influence of the duration of participation at the learning center, the diversity of the courses selected, and the impact of the diverse roles played by older people on their well-being, loneliness, and self-esteem. The results revealed that a longer participation duration resulted in higher well-being and self-esteem among participants; moreover, participating in a greater diversity of courses resulted in lower loneliness. Furthermore, increased diversity of the roles played was associated with increased well-being and self-esteem and reduced loneliness. This study explored the relationship between the learning characteristics of older learners and various critical psychological variables.